2021
DOI: 10.1016/j.jfineco.2021.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Labor leverage, coordination failures, and aggregate risk

Abstract: This paper studies an economy where demand spillovers make firms' production decisions strategic complements. Firms choose their operating leverage trading off higher fixed costs for lower variable costs. Operating leverage governs firms' exposures to an aggregate labor productivity shock. In equilibrium, firms exhibit excessive operating leverage as they do not internalize that an economy with higher aggregate operating leverage is more likely to fall into a recession following a negative productivity shock. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Investors with different views argue that debt is needed to increase the company's operating capital and if its use is optimized by the company such as managing assets, then the company has the opportunity to increase sales. Increased sales result in high corporate profits, so this information receives a positive response from investors which results in an increase in demand for the company's shares (Bouvard & de Motta, 2021). The results of this study are in accordance with the results of previous research conducted by (Z. Li et al, 2020) which shows that the Financial leverage ratio variable has no effect and is not significant to Earning per share, but is different from the results of research conducted by (Z.…”
Section: Effect Of Financial Leverage On Earning Per Sharementioning
confidence: 99%
“…Investors with different views argue that debt is needed to increase the company's operating capital and if its use is optimized by the company such as managing assets, then the company has the opportunity to increase sales. Increased sales result in high corporate profits, so this information receives a positive response from investors which results in an increase in demand for the company's shares (Bouvard & de Motta, 2021). The results of this study are in accordance with the results of previous research conducted by (Z. Li et al, 2020) which shows that the Financial leverage ratio variable has no effect and is not significant to Earning per share, but is different from the results of research conducted by (Z.…”
Section: Effect Of Financial Leverage On Earning Per Sharementioning
confidence: 99%
“…Taussig and Akron (2016) found that OL impacts manufacturing firms only when returns to scale are high. Bouvard and De Motta (2021) find that firms often exacerbate their OL because they do not internalize the negative implications they will consequently suffer in the case of a recession. OL is also employed to explain value premium , and is found to account for higher stock returns only when OL levels are relatively low (Guthrie, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%